Sistem Zonasi dan Sekolah Favorit (Pergeseran Profil Sekolah Favorit Pasca Sistem Zonasi) - Bela, Aisyah; Haryanto, Budi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The zoning system is a policy set by the government in order to minimize inequality in the quality of education. The implementation of the zoning system has both positive and negative impacts. This research aims to find out the phenomenon of student profiles in favorite junior high schools in the era of the zoning system. The method used in the research is qualitative with a phenomenological approach. Data were collected through observation, interviews, and documentation. Data analysis went through four stages: data collection, data condensation, data presentation, and conclusion drawing/verification. Test the validity of the data using the triangulation of sources and techniques.